Pengaruh Kepemimpinan Kepala Sekolah dan Kompetensi Pedagogik Guru terhadap Hasil Belajar Siswa SMK PGRI 11 Ciledug pada Kota Tangerang Banten - Muhammad As’ad; Ely Anita; Yulianto Yulianto (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
For the Effect of Principal Leadership and Teacher Pedagogical Competence on the learning outcomes of SMK PGRI 11 Ciledug students in Tangerang City, Banten, the method used was quantitative and questionnaire distribution using saturated samples. By using a statistical formula in which Variable X1 is the number of scores from respondents' questions about Principal Leadership and Variable X2 is the number of scores from respondents' questions about teacher pedagogical competencies and Y variable is the number of scores from respondents' questions about student learning outcomes. From the results of the comparison of t count (-8,202) and t table (1,995) then t count> t table means a negative significant effect between the principal's leadership on student learning outcomes. From the results of the comparison of t arithmetic 16.972 and t table 1.995, t count> from t table means a positive significant effect between teacher pedagogical competencies and student learning outcomes. From the results of the comparison of F count 2.116 F, table 0.309 then F count> F there is a significant influence between the leadership of the principal and the competent teachers of teachers on student learning outcomes..